The Relationship Between Thyroid Function and Metabolic Syndrome and Its Components: A Cross-Sectional Study in a Chinese Population - He, Jiaji; Lai, Yaxin; Yang, Jing; Yao, Yongli; Li, Yongze; Teng, Weiping; Shan, Zhongyan (Frontiers in Endocrinology, 2021)
Objective: This study aims to explore the relationship between thyroid function status and the prevalence of metabolic syndrome in the Chinese population. Methods: Cross-sectional data were obtained from the Thyroid Disease, Iodine Nutrition and Diabetes Epidemiology (TIDE) Survey. A total of 62,408 subjects aged ≥18 years were enrolled. The study was divided into a questionnaire survey and clinical data collection, including physical measurements, serum thyroid function and metabolic indicators. The number of subjects randomly selected from the normal thyroid function population, as the control group, corresponded to the number of thyroid dysfunction patients to eliminate the influence of quantity differences. Differences in metabolic indicators and the prevalence of metabolic syndrome according to sex and thyroid function status were compared. Logistic regression was used to analyze the influence of thyroid function on metabolic syndrome and its components. Results: The prevalence of metabolic syndrome was generally higher in men than in women. Overt hyperthyroidism and subclinical hypothyroidism had a significant effect on metabolism in men. Body mass index (BMI), waist circumference, and triglycerides (TGs) were significantly lower in men in the overt hyperthyroidism group, while BMI, waist circumference, systolic blood pressure (SBP) and TGs were higher in men in the subclinical hypothyroidism group than in men in the normal group. Overt and subclinical hypothyroidism had significant impacts on metabolic components in women. BMI, waist circumference, TGs, SBP and DBP in the subclinical and overt hypothyroidism groups were significantly higher than those in the euthyroid group in women. The relative risk of abdominal obesity and hypertriglyceridemia was increased in women with hypothyroidism. Thyroid dysfunction had different effects on metabolic syndrome and its components before and after amenorrhea. Conclusion: Thyroid function had important effects on the prevalence of metabolic syndrome. Women with hypothyroidism, especially post-amenorrhea women, had a higher risk of metabolic syndrome than men.